Medieval archetypes and Balkan nationalisms in the wars in 1912-1913 - Комсалова, Румяна (Balcanica Posnaniensia. Acta et studia, 2012)
The Medieval Balkans are characterized by three basic imperial archetypes – Byzantine ecumenism and the imperial ideas of Bulgarians and Serbs. The Byzantine political doctrine based upon the idea that the empire is called upon to impose the Christian religion over the barbarian worlds was transformed throughout the period of the Balkan Revival into the so-called „Megali idea” and found its reflection in the political goals of the Greek Kingdom during the Balkan Wars. The Bulgarian Medieval archetype, expressed in Simeon’s idea of a Bulgarian-Byzantine empire with Constantinople as its capital and in the concept that took shape in the ХІІІ-th century of „Tarnovo – the Third Rome”, gave Paisii Hilendarski grounds to provoke the national self-conscience. The apogee of Renaissance aspirations, San Stefano Bulgaria, was not realized but it gave birth to the myth of „Bulgaria bordering three seas”, which pushed Bulgaria into the wars as a road to national union. The third „player” on the Balkan scene – the Kingdom of Serbia in its turn sought its grounds in Stefan Dushan’s empire and its Renaissance version – the „ Načertanije” of Ilija Garašanin. Thus, the Balkan union, created in the name of a noble and just cause – to liberate their Christian „brothers” from the oppression of the Ottoman Islamic Empire, turned out in its very bud to be on mined  land by these projects imperial in their nature.